Dual modal ultra-bright nanodots with aggregation-induced emission and gadolinium-chelation for vascular integrity and leakage detection. (January 2018) - Feng, Guangxue; Li, Jackson Liang Yao; Claser, Carla; Balachander, Akhila; Tan, Yingrou; Goh, Chi Ching; Kwok, Immanuel Weng Han; Rénia, Laurent; Tang, Ben Zhong; Ng, Lai Guan; Liu, Bin
Abstract: The study of blood brain barrier (BBB) functions is important for neurological disorder research. However, the lack of suitable tools and methods has hampered the progress of this field. Herein, we present a hybrid nanodot strategy, termed AIE-Gd dots, comprising of a fluorogen with aggregation-induced emission (AIE) characteristics as the core to provide bright and stable fluorescence for optical imaging, and gadolinium (Gd) for accurate quantification of vascular leakage via inductively-coupled plasma mass spectrometry (ICP-MS). In this report, we demonstrate that AIE-Gd dots enable direct visualization of brain vascular networks under resting condition, and that they form localized punctate aggregates and accumulate in the brain tissue during experimental cerebral malaria, indicative of hemorrhage and BBB malfunction. With its superior detection sensitivity and multimodality, we hereby propose that AIE-Gd dots can serve as a better alternative to Evans blue for visualization and quantification of changes in brain barrier functions.